Kurikulum Perguruan Tinggi Nahdlatul Ulama Berbasis Wasathiyah - Wahab, Abdul; Hidayat, Muslih; Saefudin, Ahmad; Rahmawati, Dian (Edukasi Islami: Jurnal Pendidikan Islam, 2023)
This article discusses the curriculum content based on wasathiyah (moderation) in Nahdlatul Ulama (NU) College. This study uses a qualitative research approach, relying on documentation, observation, and surveys. The research identifies the content of wasathiyah values in the PAI Unisnu Jepara’s curriculum and explains values are internalized in the teaching process. The study finds that the content of wasathiyah values supporting the university curriculum includes tolerance (tasamuh), democracy (syura), peace (islah), nationalism (muwathanah), moderation (tawassuth), and respect for tradition and culture (i'tiraf bi al-'urf). These values are instilled through the use of cooperative learning methods. The results is confirm that NU, as a representation of moderate Muslim organizations in Indonesia, prioritizes the principle of religious moderation. NU has resolved the relationship between religion and the state. By adhering to the principle of muwathanah, Indonesia, based on Pancasila, is final and cannot be replaced by any other ideology, including Islamism. This study has important implications for education and Indonesian society. Wasathiyah-based education can help promote the formation of tolerant, democratic, peaceful, nationalist, moderate, and respectful characters. In addition, wasathiyah education can strengthen Indonesia as a country based on Pancasila and prevent society from radicalism